2020
DOI: 10.1017/s1463423620000584
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the use of the internet on quality of life in older adults: review of literature

Abstract: Aim: Given the paucity of data on the use of internet and quality of life (QoL), this literature review aimed to identify the motivations and barriers for internet use and the impact on QoL on older adults using the internet. Background: Even though older adults are increasingly using information technology, the numbers remain quite small globally. Currently published research primarily focuses on the various ways and methods of information technology use by older adults and the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
(35 reference statements)
3
21
0
1
Order By: Relevance
“…The current study found the effects of frequency of use to be highly significant ( p < 0.001 for QoL, and p = 0.01 for depression). While the majority of previous (pre-pandemic) studies have found similar relationships [ 9 , 14 ], some studies found no effects [ 24 ]; other discordant findings have been noted pre-pandemic, particularly for QoL [ 14 ]. Thus, the highly significant relationships between frequency of use and both QoL and depression symptoms identified here might be at least partly attributable to the social distancing and lockdown restrictions that were in place, supporting the notion that internet usage might be of particular benefit under these circumstances.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The current study found the effects of frequency of use to be highly significant ( p < 0.001 for QoL, and p = 0.01 for depression). While the majority of previous (pre-pandemic) studies have found similar relationships [ 9 , 14 ], some studies found no effects [ 24 ]; other discordant findings have been noted pre-pandemic, particularly for QoL [ 14 ]. Thus, the highly significant relationships between frequency of use and both QoL and depression symptoms identified here might be at least partly attributable to the social distancing and lockdown restrictions that were in place, supporting the notion that internet usage might be of particular benefit under these circumstances.…”
Section: Discussionmentioning
confidence: 91%
“…The current study provides valuable insight by exploring effects in a large, well-characterised sample, allowing important covariates (e.g., household wealth, education) to be controlled for. Further, well-validated outcome measures were used; this has been noted as a weakness of many previous studies into QoL in particular [ 14 ]. Frequency of internet use was seen to be high; when questioned about their internet use during the coronavirus outbreak, 57% reported using the internet more than once a day, and 45% reported using the internet more than before the outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the importance of developing and maintaining good social networks increases with age (Nahm & Resnick, 2001 ; Nahm et al, 2004 ), older adults are increasingly likely to become socially isolated as their social networks decrease due to various factors, including the death of families and friends, disability, reduced mobility, and geographic relocation (Livingston, 2019 ; Mellor et al, 2008 ; Nahm & Resnick, 2001 ; Nahm et al, 2004 ). The internet can help older adults improve their social networks by circumventing some restrictions in communication (Aggarwal et al, 2020 ; Choi et al, 2012 ; Woodward et al, 2011 ). During the COVID-19 pandemic, however, many older adults have experienced both digital and social exclusions, since their lack of access to and skill with digital technologies has increased their social isolation (Seifart et al, 2021 ).…”
mentioning
confidence: 99%
“…Although older adults are less likely than their younger peers to engage in computer and internet usage (Anderson & Perrin, 2017 ; Macdonald & Hulur, 2021 ; Zickuhr & Madden, 2012 ), such technological skills can be learned and adopted (Rosenthal, 2008 ; Sayago et al, 2013 ; Winstead et al, 2013 ). Many computer and internet intervention programmes have been shown to positively influence participants' social networks or social connectedness (Aggarwal et al, 2020 ; Chen & Schulz, 2016 ; Gardiner et al, 2018 ; Ibarra et al, 2020 ).…”
mentioning
confidence: 99%